2022
DOI: 10.3390/foods11193146
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volatile Compounds, Composition, and Thermal Behavior of Coffee Beans According to Variety and Roasting Intensity

Abstract: This study aimed to investigate the ways in which the thermal behavior, composition, and volatile compound contents of roasted coffee beans depend on variety and roasting intensity. The thermal analysis revealed various transformations in coffee composition, namely, drying, water loss, and decomposition of polysaccharides, lipids, amino acids, and proteins. The results showed that volatile compounds are released differently in coffee depending on coffee type and degree of roasting. The most abundant volatile c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…The GC-MS results revealed that the majority of the chemical compounds were caffeine, which belongs to the purine group and is commonly found in coffee extracts [ 45 ]. However, the amount of caffeine detected in this study was considerably higher than in some previous studies [ 46 , 47 , 48 ]. A previous study also reported that Robusta seeds contain 40–50% more caffeine than Arabica seeds [ 49 ].…”
Section: Discussioncontrasting
confidence: 91%
“…The GC-MS results revealed that the majority of the chemical compounds were caffeine, which belongs to the purine group and is commonly found in coffee extracts [ 45 ]. However, the amount of caffeine detected in this study was considerably higher than in some previous studies [ 46 , 47 , 48 ]. A previous study also reported that Robusta seeds contain 40–50% more caffeine than Arabica seeds [ 49 ].…”
Section: Discussioncontrasting
confidence: 91%
“…Similarly, observed a group of alcohols, aldehydes, ketones, esters, hydrocarbons, pyrroles, furans, and other compounds in green Arabica beans. However, no furans were detected in our green samples, and according to, furans are formed during the roasting of the beans through the Maillard reaction. Studies on green coffee have indicated that the majority of volatiles belong to the aldehyde class. , The volatile fraction of coffee beans is known to primarily consist of alcohols, acids, esters, and aldehydes .…”
Section: Resultsmentioning
confidence: 99%
“…Volatiles were collected using a ‘push–pull’ dynamic headspace collection system. Volatiles were collected from unroasted coffee samples to assess the biochemical makeup of each coffee prior to manipulation by the roasting process 24,25 . Coffee samples (3.5 g) were ground in a ball mill (Retsch Mixer Mill MM 400, Verder Scientific Inc., Newton, PA, USA) for 3.5 min and then loaded into glass tubes (2.5 cm i.d., 61 cm long, 300 mL volume) connected to the collection system.…”
Section: Methodsmentioning
confidence: 99%
“…Volatiles were collected from unroasted coffee samples to assess the biochemical makeup of each coffee prior to manipulation by the roasting process. 24,25 Coffee samples (3.5 g) were ground in a ball mill (Retsch Mixer Mill MM 400, Verder Scientific Inc., Newton, PA, USA) for 3.5 min and then loaded into glass tubes (2.5 cm i.d., 61 cm long, 300 mL volume) connected to the collection system. Purified air was pushed into one end of the tube and pulled via a vacuum pump over the sample and through a glass column connected to the outlet end of the tube.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%